Bridging romantic and modern eras: structural elements in Byron’s She Walks in Beauty and Auden’s The More Loving One - Darmawan, Rizki; Farani, Yasmin; Putra, Suatmo Pantja (Universitas Merdeka Malang, 2024)
This study presents a comparative structural analysis of two renowned poems, “She Walks in Beauty